Representative Public Administration as the Modelling Behaviour for the New Bureaucracy - Mirko Pečarič (Central European Public Administration Review)
There is a widespread belief that the states and markets are not the omnipotent institutions. Although public participation is gaining importance, this paper argues that in the present situation liberal and democratic elements can be fastest achieved by promotion of values in the public administration. The idea is built on a notion of active representative bureaucracy, while passive representation of the society should be still under the rule of law and/or merit system of hiring public servants. The proposed strategy in a time of austerity is somehow illogical, but it could be efficient: more public funds should be given in education, (re)training and practical experiments of the good practices from other states should become more relevant. Although in our time – when reductions of public funds and dismissals of employees are present – it will be difficult to achieve this goal, we should not forget that humanity has never depended on finances; the public trust, awareness, faith and other values are all the more needed in the time of crisis. We should start from ourselves as individuals to proceed towards the benefits of community.